Biological characterisation of yellow fever 17D strain plaque variants (2009)
The Colombian 17D vaccine contains at least four phenotypes denominated small (0.3 - 1.2 mm), medium (1.3 - 2.1 mm) large (2.2 - 3.0 mm) and extra-large ( and gt;3.1 mm). These phenotypes composition and percentage distribution vary between different production lots and between ampoules from a particular lot. Each variant was cloned by diluting the vaccine and its virulent effect was analysed in young mice. The small plaque phenotype was slightly under represented in the lots analysed and showed similar virulence to the neurotropic French wild strain (LD50 and gt;10-6), whilst the medium- sized phe-notype predominated and was the most attenuated (LD50:10-4). The large and extra-large phenotypes showed intermediate virulence (LD50:10-5) regarding the others. Sequence analysis of variants within the region between the 3'NS5 end and the beginning of 3'NCR showed the closeness between those variants having some degree of virulence and between the attenuated variant and the Colombian vaccine. The 17D vaccine's heterogeneity constitutes evidence of RNA virus quasi-specie structure and shows how adverse yellow fever vaccine reaction can be associated with applying vaccines produced from attenuated viral strains.